Combating tobacco caterpillar, Spodoptera litura (Fab.) through isolated strains of Streptomyces from the soils of Kerala and Tamil Nadu - Elanchezhyan , K; Aswathy, J; Allwin , L; Rajinimala, N; Anandhi, P; Abdul Razak, T (Plant Science Today, 2024)
The tobacco caterpillar, Spodoptera litura (Fab.) is a polyphagous pest on agricultural and horticultural crops. Biological control is an effective and sustainable alternative to insecticides for insect pest management. Now-a-days, microbial compounds are used for the management of insect pests and they are the good alternative to inorganic pesticides. The various microbial control agents are obtained from the different microorganisms, actinomycetes specifically the filamentous Streptomyces produce metabolites possessing insecticidal activity. The Streptomyces is a Gram-positive multicellular bacteria and they possess numerous secondary active metabolites. The soil samples were collected from different locations in Kerala and Tamil Nadu states, India. Isolation of Streptomyces was carried out by serial dilution of 10-4 and pour plating method. The Streptomyces can be cultured in International Streptomyces Project 2 fermentation broth. The Streptomyces sp. such as S. katrae (ST 1), S. acidiscabies (ST 3), S. andamanensis (ST 5) and S. cerasinus (ST 7) were isolated from the soils of Kerala and Tamil Nadu, India by 16S rDNA sequencing and matched with Streptomyces sp. using NCBI BLAST program and were screened against 1st and 2nd instar larvae of S. litura. The strain S. katrae (ST 1) and a consortium of all the strains (ST 1 + ST 3 + ST 5 + ST 7) exhibited 66 - 70 % mortality of 1st instar larvae and 70-74 % mortality of 2nd instar larvae of S. litura. The presence of secondary active metabolites in the ISP 2 fermentation broth exhibited strong larvicidal activities and these findings indicate that the ISP 2 fermentation broth of S. katrae and the consortium possess the ability to control the pest populations at the desirable level.